The Environmental Impact of Sieben Linden Ecovillage - Bocco, Andrea (Taylor & Francis, 2019)
The present study was born out of an agreement between the Sieben Linden community (Siedlungsgenossenschaft Ökodorf e.G.) and the Politecnico di Torino (DIST), approved on May 9, 2013. The Politecnico team, led by professor Andrea Bocco, intended to perform an overall analysis of the way of living in the ecovillage, including a number of areas among which are agriculture, biodiversity, building, decision-making, diet, economy, energy, land husbandry, etc. The Sieben Linden community, on the other hand, was particularly interested in having a new ecological impact assessment done, a dozen years after that by the University of Kassel (Dangelmeyer et al. 2004).